KEPASTIAN HUKUM JUAL BELI DAN PENDAFTARAN TANAH YANG DILAKUKAN TANPA AKTA PEJABAT PEMBUAT AKTA TANAH (PPAT) - Lazuardi, Lazuardi; Widyanti, Amelia Nur; Syakura, Furcony Putri (SINERGI : Jurnal Riset Ilmiah, 2024)
The practice of under-the-table land transactions without involving a Notary Public (PPAT) is still prevalent in society. The absence of an authentic deed as legal proof of the transfer of land rights raises a number of legal issues. This study aims to examine the legal status of land transactions without a PPAT deed and its implications for legal certainty in land registration. The research questions are: What is the legal status of land transactions without a PPAT deed and What is the legal certainty of land transactions and registration that are not carried out without a PPAT deed The theories used in this research are the Theory of Legal Certainty according to Jan Michiel Otto and the Theory of Land Registration according to Boedi Harsono. The methodd used in this research is normative juridical research, specifically a library law research or secondary data with primary, secondary and tertiary legal sources. As for the research approached used combines statutory, conceptual, analytical, and case-based approaches. The method of collecting the legal materials are carried out by identifying and taking an inventory of positive laws, journals, and other legal sources. The method used in analyzing legal materials (interpretation), encompassing grammatical, systematic, analogical, refining, argumentum a contrario, and legal construction methods. From the research results, it can be concluded that land transactions conducted without a deed authenticated by a Notary Public (PPAT) have the potential to lead to various legal problems, including difficulties in land registration and the risk of ownership disputes. Based on these findings, the research provides policy recommendations to enhance legal certainty in land transactions, such as expanding access to PPAT services and simplifying registration procedures. Thus, it is expected that a more transparent, accountable, and legally protective land registration system can be established for all parties involved in land transactions